A coarse-grained model for free and template-bound porphyrin nanorings - Morley, D; Malfois, M; Kamonsutthipaijit, N; Kondratuk, D; Anderson, H; Wilson, M (American Chemical Society, 2017)
Coarse-grained simulation models are developed to study both template-bound and free porphyrin nanoring systems. Key interactions are modelled with relatively simple (and physically-motivated) energy functions which allow for relatively facile transfer both between different ring sizes and between the template-bound and free nanoring systems. The effects of varying the model parameters on the respective radii of gyration are determined. The effects of including different templates on the ring structure are investigated both in terms of the detailed geometry of the template and the interaction strength between the template and the metal centres in the nanorings. The role of the template-nanoring interaction strength in controlling potential ``caterpillar track'' rotational motion is discussed. The relationship of the model to experimental small-angle X-ray, exchange spectroscopy and electron spin resonance results is discussed.